How do Requirements Evolve over Time? A Case Study Investigating the Role of Context and Experiences in the Evolution of Enterprise Software Requirements. (June 2018) - Schneider, Stephan; Wollersheim, Jan; Krcmar, Helmut; Sunyaev, Ali
In recent years, organizations have increasingly sourced cloud-based enterprise software (ES). Although comprehensively capturing organizations' requirements considerably affects the success of an ES sourcing project, little is known about how requirements evolve beyond the implementation. We conduct a longitudinal, exploratory single-case study of the life cycle of cloud-based ES in a medium-sized organization. Over 5 years, we trace the evolution of requirements throughout the ES life cycle, beginning with the initial adoption decision and ending with considerations to retire the ES. We develop a process theory that explains how requirements evolve beyond ES implementation and throughout its life cycle. We isolate nine mechanisms that explain how contextual factors and experiences are intertwined and shape the evolution of requirements. We then develop seven propositions that explain how sourcing cloud-based ES alters the mechanisms that shape the evolution of requirements. Our findings emphasize that the evolution of requirements for cloud-based ES follows similar mechanisms to that of the requirements for on-premises ES but changes how particular mechanisms manifest. Sourcing cloud-based ES changes the influence of business divisions in acquisition and configuration activities, the role of upgrade and customization procedures, and the influence of the ES' ecosystem.